2020
DOI: 10.1186/s13075-020-02273-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cutaneous reactions to allopurinol in Kinh Vietnamese: results from a case-control study

Abstract: Objective: The aim of this study was to investigate risk factors for cutaneous adverse reactions (CARs) in Kinh Vietnamese. Methods: All patients were prospectively recruited in Ho Chi Minh City. Presence of the HLA-B*58:01 allele was determined by real-time PCR-sequence-specific amplification by using the PG5801 Detection Kit (Pharmigene, Taipei). Patients with severe (SCARs) and mild (MCARs) CARs and controls were compared for differences in features prospectively collected, and odds ratios (ORs) with 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…It is well known that the presence of HLA-B * 58:01 is closely related to the occurrence of severe adverse drug reactions (SJS, SJS/TEN, TEN, and DRESS) in the skin of patients (SCARs) when ALP is used for gout treatment, especially for Black and Asian people rather than white people [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 29 ]. Previous studies have found that the frequency of the HLA-B * 58:01 allele in patients with ALP-induced SCARs in Han Chinese, Taiwanese, Thai, Korean, Japanese and Vietnamese populations varies between 90% and 100%, while the frequency of the HLA-B * 58:01 allele in healthy people is 6–10%, depending on the ethnic population [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, the HLA-B * 58:01 allele has been approved as a diagnostic marker for ALP-induced SCARs, and its screening is recommended before using ALP for gout treatment [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that the presence of HLA-B * 58:01 is closely related to the occurrence of severe adverse drug reactions (SJS, SJS/TEN, TEN, and DRESS) in the skin of patients (SCARs) when ALP is used for gout treatment, especially for Black and Asian people rather than white people [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 29 ]. Previous studies have found that the frequency of the HLA-B * 58:01 allele in patients with ALP-induced SCARs in Han Chinese, Taiwanese, Thai, Korean, Japanese and Vietnamese populations varies between 90% and 100%, while the frequency of the HLA-B * 58:01 allele in healthy people is 6–10%, depending on the ethnic population [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, the HLA-B * 58:01 allele has been approved as a diagnostic marker for ALP-induced SCARs, and its screening is recommended before using ALP for gout treatment [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in a Han Chinese population showed that 100% of ALP-treated patients with gout and MCARs carry the HLA-B * 58:01 allele [ 12 ]. However, another study on Kinh Vietnamese reported that only approximately 6.8% of a total of 75 patients with gout and MCARs were positive for the HLA-B * 58:01 allele [ 20 ], a frequency that is almost equal to that observed in healthy Kinh Vietnamese individuals (6.5%). In this study, we found that the frequency of the HLA-B * 58:01 allele in Vietnamese patients with ALP-induced MCARs was 38.1%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations